Quantifying quality specialization across space: Skills, sorting, and agglomeration - CHANG, Pao-Li (Institutional Knowledge at Singapore Management University, 2019)
We quantify the supply-side determinants of quality specialization across space. Specifically, we complement the quality specialization literature in international trade and study how larger cities specialize in higher-quality goods within a country. In our general equilibrium model, firms in larger cities produce goods with higher quality, because agglomeration benefits accrue more to skilled workers who are also more efficient in upgrading quality. Two channels are at work in our model. The first channel is through the treatment effect of agglomeration, such that firms become more productive if they locate in a larger city. The second channel works through sorting, in that more pro-ductive firms receive higher agglomeration benefits and endogenously sort into larger cities. These two effects are further mitigated by the increasing skill premium with respect to city size, though the latter is dominated in the spatial equilibrium. Using firm-level data from China, we structurally estimate the model and find that product quality is on average 23% higher in big cities than that of small cities. We further find that agglomeration forces account for half of the quality difference in big cities while sorting of firms accounts for another half. A counterfactual policy to relax land use regulation in housing production raises the quality of goods produced in big cities by 5.5% and (in-direct) welfare of all residents by 6.2% through reallocation of economic activities across space.